Lifestyle habits, health indicators and sociodemographic factors associated with health-related quality of life and self-esteem in adolescents - Jiménez-Boraita, Raúl; Gargallo Ibort, Esther; Dalmau, José María; Arriscado Alsina, Daniel (Clinical Child Psychology and Psychiatry, 2024)
Background Mental health is defined as a state of emotional, psychological, and social well-being, and has been shown to be positively associated with self-esteem and quality of life. It is important to note that mental health is dynamic and influenced by a wide range of social, biological, and behavioral factors. Therefore, the aim this study was to describe the health-related quality of life and self-esteem in adolescents, examining their relationship with various health indicators, lifestyle habits, and sociodemographic variables. Method A cross-sectional study was conducted with a representative sample of 761 students (14.51 ± 1.63 years). Health-related quality of life, self-esteem, satisfaction with body image, adherence to the Mediterranean diet, physical activity practice, hours of nightly sleep, maximum oxygen consumption, body mass index, academic performance, and various sociodemographic factors of all participants were analyzed. Results Regression analysis showed that body satisfaction and academic performance were associated of both health-related quality of life and self-esteem. Additionally, physical activity, age, and favourable settings for physical activity engagement were also found to be related to health-related quality of life, whilst adherence to the Mediterranean diet, hours of nightly sleep, maximum oxygen consumption and socioeconomic status were associated with self-esteem. Conclusions Given the associations found between health-related quality of life and self-esteem with lifestyle habits and sociodemographic indicators, there is an urgent need to develop interdisciplinary and cross-cutting promotion strategies to improve the mental health of adolescents.
Keywords: quality of life; self-esteem; mental health; adolescence; lifestyle habits; Scopus; JCR